2017
DOI: 10.1093/annonc/mdx066
|View full text |Cite
|
Sign up to set email alerts
|

CDX2 prognostic value in stage II/III resected colon cancer is related to CMS classification

Abstract: Our work suggests that combination of the consensual CMS classification and lack of CDX2 expression could be a useful marker to identify CMS4/CDX2-negative patients with a very poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
43
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 21 publications
11
43
4
Order By: Relevance
“…With regard to CDX2 expression, it should be noted that the CDX2‐negative tumors represent a larger fraction in this cohort compared with the original Dalerba et al cohort . Our results are in concordance with recent studies that exhibited higher expression rates of CDX2 absence/loss in stage II tumors . Nevertheless, our results confirm the role of CDX2 expression as a prognostic factor, as has been previously demonstrated, and also display its correlation to tumor location.…”
Section: Discussionsupporting
confidence: 93%
“…With regard to CDX2 expression, it should be noted that the CDX2‐negative tumors represent a larger fraction in this cohort compared with the original Dalerba et al cohort . Our results are in concordance with recent studies that exhibited higher expression rates of CDX2 absence/loss in stage II tumors . Nevertheless, our results confirm the role of CDX2 expression as a prognostic factor, as has been previously demonstrated, and also display its correlation to tumor location.…”
Section: Discussionsupporting
confidence: 93%
“…Initial studies have found an association between lack of CDX2 expression and reduced survival in dMMR colorectal cancer (CMS1/immune subtype). Some studies have reported discordant results. Olsen and colleagues found that low CDX2 protein or mRNA expression was not associated with recurrence risk in a study of 119 patients with colorectal cancer, including 44 dMMR tumours.…”
Section: Discussionmentioning
confidence: 99%
“…MIR31HG expression was used to define MIR31 outliers as samples with expression higher than median ( x MIR 31 HG ) + 3 × MAD ( x MIR 31 HG ) where x MIR 31 HG represents either 2italiclog2 justRMA signal values (microarray) or normalized read values (sequencing) and MAD represents the corresponding within‐dataset cross‐sample median absolute deviation. Samples with CDX2 expression below the 15.6% percentile in each dataset were classified as CDX2 negative . CMS labels for pCRCs from the CIT, LICR and TCGA (COADREAD) datasets were retrieved from Sage Bionetworks Synapse (identifier syn4978511).…”
Section: Methodsmentioning
confidence: 99%